EduAssist: Interactive Educational Assistant - Hibatin Wafirah Che Rahim; Kamilia Karmila Kamarulariffin; Nur Hayatun Shahida Norizan; Mohamad Rahimi Mohamad Rosman (Malaysia Journal of Invention and Innovation, 2023)
EduAssist is a system that is designed to assist university students in arranging their daily work and time as a student. This system allows users, which are students and lecturers, to upload materials that students require for their studies, such as self-notes, their routine activities information, and any important dates. There are still many university students who lack skills in daily life management and have forgotten about the importance of day-to-day life management. Some students are unable to manage their time well while they are in university. Therefore, the objectives of this system are to help students plan their daily life, arrange their time to improve student access and retrieval of notes, and ease students in obtaining notes, assessments, and activities planners all in one place. Hence, this system can help students to solve daily management and increase their awareness of the importance of everyday life management as a student. Also, it can assist university students in managing their time management and arranging their tasks properly.